Implementasi Al-Amin Digital Learning System dalam Hasil Evaluasi Pembelajaran Fikih di MTs Pesantren Al-Amin Mojokerto - Nisa', Khoirun; Pangestu, Muhammad Noval; Zulfah, Machnunah Ani (Institute of Research and Public Service Universitas Jenderal Soedirman, 2023)
In today's technological age, the appraisal process is often considered inefficient. The teacher has to correct the answer sheets one by one, and it will take a very long time. Technology use is likely to help teachers in a more effective evaluation process. This study aimed to determine how ADILS was implemented in the evaluation results of fikih learning at MTs Al-Amin Islamic Boarding School and the supporting and inhibiting factors for implementing ADILS in learning evaluation activities. This research was a descriptive qualitative research. The data sources used in this study are primary data sources and secondary data sources. Researchers used observation, interviews, and documentation to obtain the data needed for research. MTs Al-Amin Islamic Boarding School first analyzes the needs and preparations before implementing ADILS. After that, the school will hold training for teachers and students. Then, the evaluation will be implemented using ADILS. The advantages of ADILS are that it makes it easier for teachers to get student evaluation results. The drawback is that some students have decreased motivation because they are not careful and precise in answering questions. The application of ADILS can help evaluation activities become more effective and efficient. The teacher does not need to correct the answer sheets one by one. However, the teacher can immediately find the evaluation results in the ADILS application.